EDUGAME "THE WORLD OF WORD" IN LEARNING ENGLISH IN THE 21ST CENTURY - Fahrul Rizal Ichal (IJLECR (International Journal of Language Education and Cultural Review), 2020)
Abstract : In this 21st century many people lack knowledge of English vocabulary, which is an important language just like any other language. Therefore this edugame application is designed by using a combination of English vocabulary knowledge and training on how to speak English vocabulary. The making of this application uses the rational unified process methodology in making this application. This application was created using Unity 3D and Speech Recognition. This application is designed to get good results from users through the distribution of questionnaires with the results of 58% of users strongly agree that the help menu used to help users when experiencing difficulties is very easy to understand, 50% of users strongly agree that this edugame application can deepen vocabulary especially nouns English and 55% of users strongly agree that this edugame application fosters an interest in being able to speak English. Keywords: Edugame, Language, English, Vocabulary, 21st Century.